2014
DOI: 10.3389/fncir.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical criticality during induction of anesthesia in human ECoG recordings

Abstract: In this work we analyze electro-corticography (ECoG) recordings in human subjects during induction of anesthesia with propofol. We hypothesize that the decrease in responsiveness that defines the anesthetized state is concomitant with the stabilization of neuronal dynamics. To test this hypothesis, we performed a moving vector autoregressive analysis and quantified stability of neuronal dynamics using eigenmode decomposition of the autoregressive matrices, independently fitted to short sliding temporal windows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 30 publications
4
56
1
3
Order By: Relevance
“…Thus, our overarching hypothesis that dynamical criticality is essential for the responsiveness characteristic of consciousness suggests more specifically that loss of consciousness would be accompanied by a loss of criticality, an implication first preliminarily tested by Alonso et al (2014). Here we show that dynamical criticality is disrupted universally during loss of consciousness regardless of the anesthetic regimen or specific microscopic features of neuronal activity.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, our overarching hypothesis that dynamical criticality is essential for the responsiveness characteristic of consciousness suggests more specifically that loss of consciousness would be accompanied by a loss of criticality, an implication first preliminarily tested by Alonso et al (2014). Here we show that dynamical criticality is disrupted universally during loss of consciousness regardless of the anesthetic regimen or specific microscopic features of neuronal activity.…”
Section: Introductionmentioning
confidence: 66%
“…Thus, we use order 1 models for the rest of the analysis of both real and surrogate datasets (see below). Alonso et al (2014) has shown that the choice of the order of the model does not strongly affect the results. This was confirmed with this dataset as well (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Our efforts aimed at establishing a relationship between brain activity under different anesthetic regimes and the linear stability of the registered ECoG signals. Our previous studies have shown that under induction of anesthesia the dynamical stability (DS) of linear models fitted to the ECoG signals is increased and thus become less responsive, then reversed upon emergence to wakefulness 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…These measurements correspond to the synchronized activities of thousands of neurons and offer a unique window to cortex brain activity. Our previous results suggest that tracking changes in the dynamical stability of (VAR) models fitted to these signals yields a marker which covaries with the level of arousal of the subjects: the dynamical global modes of brain activity, which under normal circumstances hover between stability and instability, become more stable 17,18 . We have demonstrated that this specific hallmark is disrupted in anesthesia and restored after recovery, in humans and macaques, for two different anesthetic agents 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation